Child Aware Practice in Adult Social Services: A Scoping Review. Issue 3 (2nd July 2016) - Tilbury, Clare; Walsh, Peter; Osmond, Jennifer
Abstract: The development of "child aware" practice is about the capacity and capability of adult health and social service providers to identify and respond to the needs of children. A scoping review of the literature considered five adult adversities associated with family stress and reduced parenting capacity: mental illness, alcohol and substance abuse, homelessness, intellectual disability, and domestic violence. Although there are specific needs for children pertaining to particular adversities, there was substantial commonality of potential effects. These included emotional and psychological difficulties, physical and mental health problems, academic difficulties, language delays, peer difficulties, stigma, trauma reactions, loss and grief, instability, and social exclusion. How children react to difficulties in their family depends upon various protective factors, a child's frame of reference, and other dynamics within the family that can offset risks. The findings aim to inform policy, program development, and practice in adult social services, enhancing their responsiveness to children.